Frankincense Revisited, Part II: Volatiles in Rare Boswellia Species and Hybrids - Niebler, Johannes; Eslamieh, Jason; Büttner, Andrea (Chemistry & Biodiversity, 2016)
In this second part of the investigation of volatiles and semivolatiles in Boswellia gum resins, an additional five less common species were analyzed by (SPME-)GC-MS, namely B. ameero, B. elongata, B. neglecta, B. popoviana and B. rivae. Moreover, the results of hybridization experiments are reported in combination with the volatile composition of their gum resins. Our study shows that B. sacra benefits from an intra-specific cross-pollination, as the resulting hybrid B. sacra var. supersacra has a far higher seed germination rate and viabilit
Keywords: Boswellia; Burseraceae; Hybrid; Frankincense; Olibanum; SPME-GC-MS